2016
DOI: 10.1136/bmjopen-2015-010555
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of risk and predictive testing held by the first-degree relatives of patients with rheumatoid arthritis in England, Austria and Germany: a qualitative study

Abstract: ObjectivesThe family members of patients with rheumatoid arthritis (RA) are at increased risk of developing RA and are potential candidates for predictive testing. This study explored the perceptions of first-degree relatives of people with RA about being at risk of RA and engaging in predictive testing.Methods34 first-degree relatives (siblings and offspring) of patients with RA from the UK, Germany and Austria participated in semistructured interviews about their perceptions of RA risk and the prospect of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 44 publications
8
69
0
Order By: Relevance
“…Being aware of their risk status would allow them to react appropriately and rapidly, if symptoms such as synovial joint swelling occurred. In accordance with the study results of Stack et al (23), exploring the perceptions of risk and predictive testing held by the first-degree relatives of patients with RA, some participants suggested that ongoing support by health professionals should be offered for those who have additional questions regarding their personal risk.…”
supporting
confidence: 74%
“…Being aware of their risk status would allow them to react appropriately and rapidly, if symptoms such as synovial joint swelling occurred. In accordance with the study results of Stack et al (23), exploring the perceptions of risk and predictive testing held by the first-degree relatives of patients with RA, some participants suggested that ongoing support by health professionals should be offered for those who have additional questions regarding their personal risk.…”
supporting
confidence: 74%
“…During the early planning stages of EuroTEAM, several national RA organisations and patient groups in a range of European countries [ Table 2] were approached in order to seek endorsement of the project, provide advice and support for the funding application, and to identify potential PRPs. Additional PRPs were recruited Attending and contributing to annual scientific meetings and regular teleconferences Development of a glossary resource (WP1-4) Contributing to a meta-synthesis of qualitative literature on public perceptions of predictive testing [13,14] (WP4) Contributing to the development of interview schedules (including question setting) and the interpretation of qualitative data [12,46] (WP4) Contributing to the development of informational resources for those at risk (WP4) Evaluating a web-based platform for the communication of risk information (WP4) Developing a questionnaire for patients undergoing a lymph node biopsy procedure (WP3) Developing informational resources for patients about RA such as the 'Metaphor Project' (a collaboration between Eva C Johansson (PRP) and Dr. Heidi Wähämaa from the Karolinska Institutet) exploring the communication of scientific concepts via the use of metaphors and visual representations Contributing to the project website (e.g. providing news items and reports, creating subtitles for videos) (WP4) Developing lay summaries of EuroTEAM methods and findings (e.g.…”
Section: Patient Research Partner Involvement and Euroteammentioning
confidence: 99%
“…There has been a growing appreciation of the benefits of PPI within rheumatology research [6,7]. For example, patients have contributed to: the development of questionnaires to assess help-seeking behaviours in patients with new onset rheumatoid arthritis (RA) [8] and hypothetical reactions to the symptoms of RA amongst members of the public [9]; the development of interview schedules [10][11][12]; systematic reviews [13][14][15]; generating research ideas [16]; rheumatology conferences [17] and the development of international research recommendations [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within other cohorts, the psychological implications of an at-risk diagnosis have been reported. These have manifest as symptoms associated with anxiety and depression ( 14 16 ). Through focus group discussion and qualitative research techniques, researchers were able to demonstrate a theme of fear and uncertainty of a future diagnosis of RA ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%